Masjid sebagai Sentral Komunikasi Sosial dalam Penyebaran Informasi untuk Mendukung Pembangunan Masyarakat Islam - Awaluddin Hidayat; Muhammad Alif Al-Aziz; Mega Utami Imyansah; Lili Marzila; Wismanto Wismanto (Moral : Jurnal kajian Pendidikan Islam, 2024)
Mosques play a crucial role in the lives of Muslim communities, not only as places of worship but also as centers for disseminating information and facilitating social communication. This study aims to explore the function of mosques in spreading information and facilitating communication, both through traditional methods and modern digital technology. The research utilizes a qualitative approach, involving field studies and in-depth interviews at several mosques in urban and rural areas. The findings indicate that mosques serve as strategic hubs for conveying religious, social, and cultural information through sermons, religious lectures, and community discussions. Mosques also function as public spaces, enabling communication across different social strata and generations. In the digital era, many mosques have embraced social media to reach a wider congregation, though some rural mosques still face technological limitations. The role of mosques in spreading information and facilitating communication has positive impacts on strengthening social solidarity, enhancing religious literacy, and empowering communities. In conclusion, mosques remain vital institutions for reinforcing social cohesion and communication within Muslim communities, though challenges remain in optimizing their role in the modern era.